2008
DOI: 10.1373/clinchem.2007.102699
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of New Prostate-Specific Antigen WHO Standardization on Biopsy Rates and Cancer Detection

Abstract: BACKGROUND:Clinicians may be unaware that replacement of the historical total prostate-specific antigen (tPSA) standard with the WHO 96/670 international standard leads to difficulties in interpreting tPSA results. Our aim was to investigate the relationship between the Hybritech and WHO calibrations of the Beckman Coulter tPSA assay, and to assess the impact on prostate cancer (PCa) detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
0
20
0
1
Order By: Relevance
“…In the meantime, we must not forget the very real limitations of our current approaches: cutpoints certainly make life simpler, but rarely reflect complex biological systems adequately. In addition, as pointed out by Janssen et al (3 ), changes in calibration can importantly influence widely accepted cutpoints.…”
Section: Use Of Risk Prediction In Place Of Cutpointsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, we must not forget the very real limitations of our current approaches: cutpoints certainly make life simpler, but rarely reflect complex biological systems adequately. In addition, as pointed out by Janssen et al (3 ), changes in calibration can importantly influence widely accepted cutpoints.…”
Section: Use Of Risk Prediction In Place Of Cutpointsmentioning
confidence: 99%
“…In the last issue of Clinical Chemistry, Jansen and colleagues reported their use of the WHO-endorsed calibrator to examination the recalibration of one widely used PSA assay (3 ). Jansen et al (3 ) report that calibration affects both the likelihood that a man will undergo a biopsy procedure and the likelihood that the biopsy will reveal cancer. This report is a timely reminder that the PSA concentration, as given on a laboratory report, is not a simple statement of a true biological state but is affected by subtle details of laboratory techniques.…”
mentioning
confidence: 99%
“…Consequently, a PSA cut-off of 3.0 -3.1 μ g/L should be considered for WHO calibrated assays in order to achieve the same diagnostic effi ciency as with a cut-off of 4.0 μ g/L in traditionally calibrated assays (26) . Studies have shown that the application of the WHO standard for PSA assays with traditionally used PSA thresholds leads to a signifi cant decrease in detection of prostate cancer (27,28) . For example, applying the WHO calibration for screening a cohort of 5865 men yielded a 19 % decrease in prostate biopsies and a 20 % decrease in detected cancers compared with the " Hybritech " calibration, at a cut-off for biopsy of 4.0 μ g/L (28) .…”
Section: Example 2: Prostate-specifi C Antigenmentioning
confidence: 99%
“…Kalibratie met de WHO-standaard levert bij elke PSA-assay een PSA-uitkomst op die 20% lager ligt dan de Beckman Coulter-standaard. 18 Indien men gebruik zou maken van een assay met de WHO-standaard en een PSA-afkapwaarde van 3 ng/ml als indicatie tot biopsie hanteert, dan komt deze indicatie hoger te liggen dan die gebruikt in de ERSPC. Indien men bij de risicoberekening met behulp van de Prostaatwijzer een WHO-gekalibreerde waarde invult, dan zal de risicoberekening te laag uitvallen, omdat de PSA-waarde eigenlijk hoger is.…”
Section: Komt Er Nu Een Bevolkingsonderzoek?unclassified